Kemampuan Debitur dalam Pemenuhan Kewajiban pada Masa Pra-Permohonan Pencabutan PKPU Berdasarkan Asas Itikad Baik - Mutiara Seroja; Firdaus Firdaus; Hengki Firmanda (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2026)
This research aims to analyze the interpretation of the good faith principle in the debtor's ability to fulfill obligations during the pre-PKPU revocation request period and to understand the debtor's ability to fulfill obligations during the pre-PKPU request period based on the good faith principle. This research employs normative legal research methods (doctrinal legal research) with a statute approach, conceptual approach, and case approach. Data sources consist of primary legal materials including Law Number 37 of 2004 concerning Bankruptcy and PKPU, the Civil Code, and commercial court decisions; secondary legal materials including books, legal journals, and research results; and tertiary legal materials including legal dictionaries and encyclopedias. The research findings indicate that the interpretation of the good faith principle in the debtor's ability to fulfill obligations during the pre-PKPU revocation request period encompasses interrelated objective and subjective dimensions. The objective dimension includes financial capacity that can be measured through insolvency parameters (cash flow test and balance sheet test), while the subjective dimension includes transparency, honesty, seriousness, and constructive cooperation with creditors. Inconsistency in court decisions, as evident in the differences between Decision Number 226/Pdt.Sus-PKPU/2023/PN Niaga Jkt.Pst which rejected the revocation request and Decision Number 9/Pdt.Sus-PKPU/2023/PN.Niaga.Mks which granted it, proves the absence of standardized criteria in interpreting the good faith principle.